(untitled) (Global Journal of Science Frontier Research, 2018)
The study was conducted in Dilla substation with objective of identifying optimum between plant space for optimum seed yield and quality seed. Planting one high yielding which is in seed multiplication status was used as experimental material. Four different between plant space (10 cm, 20cm, 30cm and 40cm with constant between row space(40cm) were used as experimental treatments in a randomized complete block design (RCBD) with four replications. Plot size was 3 x 2m with an inter-row spacing of 40cm and 1m between replication and plots. Dry matter herbage yield has shown significantly higher in between plant space of 20cm than other treatments (30 and 40 cm) at (p